Knowledge, attitudes and practice of solid waste disposal among residents of a selected community in Kano State, Nigeria - Musa, Abuhuraira Ado; Abdullahi, Yusuf Muhammad; Umar, Maryam Dahiru; Bello, Shehu; Muhammad, Faisal (International Journal Of Community Medicine And Public Health, 2021)
Background: This study aimed to assess the level of knowledge, attitudes, and practice of solid waste disposal among residents of the Husuren-Kwari community in Kano, Nigeria. Methods: A non-experimental descriptive survey research design was adopted and data were obtained from June to October 2019. A simple random sampling technique was used to select 45 households as the samples. The data was collected using a semi-structured questionnaire. The data obtained were analyzed using a statistical package for social sciences software. Results: In this study, more than half (53.3%) of the respondents were ≥36 years and 80.0% of them were males. About 42.2% of the respondents had a secondary level of education and 44.4% of the respondents were farmers. Close nine-tenths (88.9%) of the respondents agreed that proper waste disposal is any means that we can get rid of unwanted materials and 84.4% know the local method of disposing of waste. Only 24.4% of the respondents were aware of the modern methods of solid waste disposal. Little above half (51.1%) of the respondents were using the burning method to dispose of the waste, and close to half (46.7%) of the respondents were dumping the waste in front of the house. Conclusions: The finding reported a poor level of knowledge, negative attitude, and poor level of practice regarding waste disposal among the people of this community. The government and non-governmental organizations should organize a massive campaign on the importance of proper waste disposal and to create awareness on proper waste disposal practices.